Perancangan Model Sistem Area Parkir Online Dengan Aplikasi Berbasis Mikrokontroler - Erby Virta Joseph Paays; Suhartati Agoes; Henry Candra (Website, 2021)
In general, the parking area system still uses a ticket paper or RFID card as a step to identify a visitor. At this time it’s too hard for finding a parking slot because the visitors can’t look easily for the parking slot, this can be caused by areas with minimal lighting. Although equipped with information on the number of available parking slots or even assisted with lights above each parking slot, that system is still not helpful because of the possibility of greater errors and are difficult to fix when a problem occurs, also to get a parking slot becomes more difficult especially during peak hours which allows increasing traffic or queues in the parking area. In this research, a parking system was designed with online-based. The visitors will receive an empty parking slot information using their cellphone. In each parking slot, there is a Light Dependent Resistor (LDR) sensor to detect which slot is empty. At the entrance gate, there is an infrared sensor and ESP 8266 module are provided to open the automatic barrier (Barrier Gate). The application that helps provide parking slot location information is expected to facilitate the search for empty parking slots for each visitor, coupled with a wi-fi connection to open the Barrier Gate which makes it easy for residents to enter the parking area. The end of this research is to test the parameters of the Received Signal Strength Indicator (RSSI) by changing the distance. This test is carried out on 2 different operators in order to conclude whether the designed system can work properly and see the response to different operators.Pada sistem wilayah parkir pada umumnya masih menggunakan karcis atau pun kartu Radio Frequency Identification (RFID) sebagai langkah identifikasi pendatangnya. Pada saat ini untuk mendapatkan slot parkir sering kali pendatang mendapatkan kesulitan karena tidak dapat melihat slot parkir dengan mudah. Meskipun sekarang sudah dilengkapi dengan informasi jumlah slot parkir yang tersedia, masih saja sistem tersebut masih kurang membantu karena kemungkinan galat yang lebih besar dan sulit untuk diperbaiki ketika terjadi masalah, bahkan untuk mendapatkan slot parkir menjadi lebih sulit terutama ketika jam sibuk yang memungkinkan menambah kemacetan atau antrian pada area parkir. Dalam penelitian ini dirancang sebuah sistem parkir online. Pengendara dapat menerima informasi slot parkir yang kosong melalui aplikasi. Di setiap slot parkir terdapat sensor Ligth Dependent Resistor (LDR) untuk mendeteksi slot mana yang kosong. Di bagian pintu masuk, diberikan sensor inframerah dan modul ESP 8266 untuk membuka Barrier Gate. Dengan adanya aplikasi yang membantu memberikan informasi lokasi slot parkir diharapkan memudahkan pencarian slot parkir yang kosong untuk setiap pengunjung. Akhir penelitian ini adalah menguji parameter Received Signal Strength Indicator (RSSI) dengan mengubah jarak. Pengujian ini dilakukan pada 2 operator yang berbeda agar dapat disimpulkan apakah sistem yang dirancang dapat bekerja dengan baik dan melihat responnya terhadap perbedaan operator.